EFFICIENCY OF ZAKAT MANAGEMENT IN BAITUL MAL BANDA ACEH: DATA ENVELOPMENT ANALYSIS APPROACH - T. Muhammad Ghufran; Muhammad Hasbi Zaenal; Endri (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2022)
Purpose – The aim of the study is to examine the level of efficiency and the total potential improvement efficiency in Baitul Mal Banda Aceh.Design/methodology/approach – To achieve this objective, the current study used the DEA to analyzes the interaction between input variables consisting of socialization costs, number of amil and operational costs with output variables consisting of the total collection and the total distribution of zakat, infaq and sadaqah of Baitul Mal Banda Aceh for the period 2018-2020.Findings – The results show that Baitul Mal Banda Aceh operated inefficient. Inefficiency occurred throughout 2018, 2019, 2020 with overall efficiency scores of 64.1%, 60.1% and 57.5%. Scale efficiency scores of 74.5%, 72.8% and 71.7%. Technical efficiency scores of 86%, 82.5% and 80.1%. Inefficiency comes from all variables, both output and input.Research limitations/implications – The study invokes the attention of government and policymakers to build up the efficiency of Baitul Mal, which in turn, leads to increased public participation to paying zakat in official Zakat Institutions. For Baitul Mal management, it is necessary to increase its efficiency. Because it is known that there are still many factors that can be optimized.Originality/value – This adds to the scarce literature on measuring efficiency of zakat management in Baitul Mal using the DEA approach. This study contributes to the literature on the issue of zakat management, variations of variables and measurement approaches by reconfirming (or otherwise) findings of previous studies.Keywords Efficiency, Zakat, Management, Baitul Mal, Banda Aceh, Data Envelopment Analysis